2009
DOI: 10.3923/pjbs.2009.526.529
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expressed Protein in Developing Stages of Nepenthes gracilis Korth. Pitcher

Abstract: Nepenthes gracilis Korth. is a member of carnivorous plants in family Nepenthaceae. The plants have beautiful and economically important pitchers. It is interesting to study the protein(s) correlated with the pitcher. Crude proteins were extracted from leaf, leaf with developing pitcher and developed pitcher of the same plant and analyzed by Sodium Dodecyl Sulfate Polyacrylamide Gel Electrophoresis (SDS-PAGE). Two protein bands with molecular weights of 42.7 and 38 kDa were obtained from young leaf and leaf wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…This study showed that pitcher formation might be correlated with the gene expressed in the leaf. Thus, this study suggests that pitcher formation is part of leaf development [28].…”
Section: Resultsmentioning
confidence: 53%
“…This study showed that pitcher formation might be correlated with the gene expressed in the leaf. Thus, this study suggests that pitcher formation is part of leaf development [28].…”
Section: Resultsmentioning
confidence: 53%